2017
DOI: 10.1002/pon.4559
|View full text |Cite
|
Sign up to set email alerts
|

Patient information in phase 1 trials: A systematic review

Abstract: Patients' decisions regarding participation in phase 1 trials are based on more than the information of the trial. The way patients express the information they have been given could be limited by the applied methods for evaluating this variable. While relatives are expected to be resources for patients entering a phase 1 trial, this topic has not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(298 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, if participating in an early phase clinical trial fits patients' values, they may be better motivated to comply to the specific obligations of a trial. Although previous systematic reviews have examined patients' perception, comprehension and understanding of early phase clinical trials [6,7] and general barriers to participate in clinical trials [8], a systematic overview of relevant patient values in this context doesto the best of our knowledgenot yet exist. Such an overview could help healthcare professionals to anticipate patient values in the consultation and thereby support patients in expressing values in light of their decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if participating in an early phase clinical trial fits patients' values, they may be better motivated to comply to the specific obligations of a trial. Although previous systematic reviews have examined patients' perception, comprehension and understanding of early phase clinical trials [6,7] and general barriers to participate in clinical trials [8], a systematic overview of relevant patient values in this context doesto the best of our knowledgenot yet exist. Such an overview could help healthcare professionals to anticipate patient values in the consultation and thereby support patients in expressing values in light of their decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…8,[26][27][28] Such studies reported high rates of enrollment among those who viewed a consent form, 29 but this may provide limited insight into other factors that shape enrollment. 30 we show here, by the time patients initiated the EP trial process, most had nearly solved the Rubik's cube of enrollment.…”
Section: Discussionmentioning
confidence: 91%
“…Outcome researchers have used pipeline models to examine enrollment, 6,30,31 barriers to enrollment, 32-34 and oncologists' role in enrollment. 17 These models have focused on factors that may cause patients to "leak out" of the trials pipeline (eg, disease progression or eligibility criteria).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of participation in phase 1 oncology trials have considered the minimal chances of a therapeutic benefit as being, from patients’ perspectives, problematic. They document that life‐threateningly ill patients overestimate the chance of cure (Catt et al, 2011; Gad et al, 2018) and misconceive what trial participation involves (Kimmelman, 2017; Miller & Joffe, 2008; Pentz et al, 2012). Thus, as Jain writes about phase 3 oncology trials, phase 1 trials ‘ghost’ the lives, death, and suffering of the majority of patients, who will never benefit from trial participation (Jain, 2010; Plutynski forthcoming).…”
Section: Introductionmentioning
confidence: 99%